2005
DOI: 10.1007/s11069-004-8891-3
|View full text |Cite
|
Sign up to set email alerts
|

Global Perspectives on Loss of Human Life Caused by Floods

Abstract: Every year floods cause enormous damage all over the world. This study investigates loss of human life statistics for different types of floods and different regions on a global scale. The OFDA/CRED Database contains data on international disasters and is maintained by the Centre for Research on the Epidemiology of Disasters in Brussels (CRED) in cooperation with United States Office for Foreign Disaster Assistance (OFDA). Information from this source on a large number of flood events, which occurred between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
470
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 772 publications
(487 citation statements)
references
References 10 publications
3
470
0
14
Order By: Relevance
“…Flooding is the most frequently occurring natural disaster in the world (Jonkman 2005). However, it is expected that flooding is going to occur even more frequently in the future as a result of climate change (Lenderink and Van Meijgaard 2008;Min et al 2011;Rojas et al 2013;Bruwier et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Flooding is the most frequently occurring natural disaster in the world (Jonkman 2005). However, it is expected that flooding is going to occur even more frequently in the future as a result of climate change (Lenderink and Van Meijgaard 2008;Min et al 2011;Rojas et al 2013;Bruwier et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of global statistics showed that inland floods (river floods, flash floods and drainage floods) caused 175,000 fatalities and affected more than 2.2 billion people between 1975(Jonkman 2005. In these statistics the consequences of other types of floods such as coastal floods and tsunamis are not included.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies investigate loss of life patterns on global scale (Berz et al 2001;Jonkman 2005) or discuss loss of life in the context of general public health impacts (Hajat et al 2003;Ahern et al 2005). Other studies focus on the analysis of the causes and circumstances of individual flood disaster deaths for specific regions or events (Coates 1999;Jonkman and Kelman 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to Kron (2002), river flooding is caused by heavy precipitation and/ or the melting of snow, making rivers overflow their banks to cover land not usually covered by water. However, river flooding may be predicted by specific methods (Jonkman 2005). While reaction time plays a major role in the management of all natural disasters, it is particularly crucial in the case of floods (Walder and O'Connor 1997).…”
Section: Introductionmentioning
confidence: 99%